2019
DOI: 10.3390/jcm8020278
|View full text |Cite
|
Sign up to set email alerts
|

Medication in AN: A Multidisciplinary Overview of Meta-Analyses and Systematic Reviews

Abstract: Drugs are widely prescribed for anorexia nervosa in the nutritional, somatic, and psychiatric fields. There is no systematic overview in the literature, which simultaneously covers all these types of medication. The main aims of this paper are (1) to offer clinicians an overview of the evidence-based data in the literature concerning the medication (psychotropic drugs and medication for somatic and nutritional complications) in the field of anorexia nervosa since the 1960s, (2) to draw practical conclusions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 204 publications
(410 reference statements)
0
37
0
Order By: Relevance
“…Thus, whereas drugs such as e.g. antidepressants 42 and antipsychotics 43 are widely prescribed for symptoms of AN, including hyperactivity 44,45 , the evidence-base for their effectiveness is meagre 2,42,43,46 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, whereas drugs such as e.g. antidepressants 42 and antipsychotics 43 are widely prescribed for symptoms of AN, including hyperactivity 44,45 , the evidence-base for their effectiveness is meagre 2,42,43,46 .…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and functional studies in patients with AN have shown alterations in insular activity and in the prefrontal cortex, orbitofrontal, temporal, parietal, anterior cingulate, and ventral striatum (nucleus accumbens, NAcc) [ 18 , 19 , 20 ]. The available evidence suggests that the two most relevant targets for the surgical treatment of AN appear to be the NAcc [ 21 ] and the subcallosal cingulate (SCC), mainly due to the substantial involvement of these two structures in the reward circuits, but also because these two areas serve as communication links between the limbic and cortical systems [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the level of evidence is low, ECT may be useful and safe for the management of severe and treatment-resistant MDD in patients with AN. Its wider accessibility compared to other brain stimulation techniques should facilitate the organization of a prospective trial, particularly in patients with severe comorbid MDD, given the lower efficacy of SSRI in AN [5]. The cognitive and memory effects of ECT are a challenging aspect.…”
Section: Current Evidence and Issuesmentioning
confidence: 99%
“…Starvation and nutritional status affect behavior, cognition, and disease symptoms. The nutritional status also influences the treatment response, especially to antidepressants that are less effective in acutely ill and underweight patients [5]. To the best of our knowledge, no study has determined whether the nutritional status affects the resting brain state and the neuromodulatory response.…”
Section: Current Evidence and Issuesmentioning
confidence: 99%
See 1 more Smart Citation